Participatory Evaluation and Promotion of Tef Production Technologies for Moisture Deficit Areas of Simada District in Amhara Region, Ethiopia - Ferede, Misganaw; Abathun, Tamir; Awoke, Yihenew (Journal of Tropical Crop Science, 2025)
Tef (Eragrostis tef Zucc. Trotter) is a small cereal crop resilient to adverse climatic and soil conditions and possesses desirable storage properties. It provides high-quality food and grows under marginal conditions which are not unsuitable for other cereal crops. Although tef is a major cultivated crop in the Simada district, demonstration and adoption of improved tef varieties and agronomic practices are very limited. Therefore, the study was initiated to select and promote the higher grain yielding tef varieties with agronomic practices and create awareness to farmers and end users. The activity was conducted on six farmers’ fields in the Simada district in the 2019 and 2020 cropping seasons. Early maturing tef released varieties, namely “Hiber-1”, “Boset”, and “Tseday” (Cr-37), and local tef varieties were used for the study in a plot area of 10m by 10m for each variety across sites. Farmers and researchers selected the “Hiber-1” tef variety due to agronomic traits and grain yield performance. “Hiber-1” was ranked 1st by farmers in both the Vertisol and Nitisol areas. It showed 31%, 28.4%, and 25.1% grain yield advantage over “Boset”, “Tseday”, and the local varieties respectively. In addition, the rank correlation of farmers’ rank and grain yield rank of the varieties showed a strong positive correlation. Therefore, the “Hiber-1” tef variety should be scaled out in the Simada district and areas with similar agro-ecologies in Amhara Region and Ethiopia.